Documenting the Diversity, Distribution, and Status of Maine Bumble Bees: The Maine Bumble Bee Atlas and Citizen Scientists - Bickerman-Martens, Kalyn; Swartz, Beth; Butler, Ron; Drummond, Francis (Maine Policy Review, 2017)
The Maine Bumble Bee Atlas (MBBA) is a multiyear (2015–2019) citizen science project coordinated by the Maine Department of Inland Fisheries and Wildlife (MDIFW) in partnership with the University of Maine. The project’s goals are to increase scientific knowledge of Maine’s bumble bee fauna and raise public appreciation for native pollinators and their conservation. Project partners accomplish these goals by training citizen scientists to conduct surveys statewide using standardized data-collection methods and by providing outreach to both project volunteers and the public on bumble bees and native pollinator conservation. During the project’s first three years, 230 volunteers have been trained to participate in MBBA at six workshops held across the state. As of the end of the second field season, MBBA citizen scientists have documented over 10,300 species records in nearly 500 townships statewide. These data have already made a valuable contribution to species status assessments conducted by MDIFW and the US Fish and Wildlife Service. MBBA staff also maintain a website, Facebook page, and blog to keep volunteers and the public informed about the project and raise awareness of, and support for, native pollinator conservation.